(untitled) (Journal of Engineering, 2011)
The aim of this research work is to study the effect of stabilizing gypseous soil, which covers vast areas in the middle, west and south parts of Iraq, using liquid asphalt on its strength properties to be used as a base course layer replacing the traditional materials of coarse aggregate and broken stones which are scarce at economical prices and hauling distances. Gypseous soil brought from Al-Ramadi City, west of Iraq, with gypsum content of 66.65%, medium curing cutback asphalt (MC-30), and hydrated lime are used in this study. The conducted tests on untreated and treated gypseous soil with different percentages of medium curing cutback asphalt (MC-30), water, and lime were: unconfined compression strength, and one dimensional confined compression under both dry and absorbed test conditions. The test results showed that stabilizing gypseous soil using the optimum fluid content of 16% (5% cutback asphalt+11% water) have improved the unconfined compressive strength, compressibility, rebound consolidation, and waterproofing of gypseous soil, but under absorbed condition the stabilized gypseous soil using cutback asphalt only did not satisfy the requirements for base course construction, therefore it was decided to use lime additive to improve the properties of soil-cutback mixture under absorbed condition.